2021
DOI: 10.18844/ijeths.v5i3.7155
|View full text |Cite
|
Sign up to set email alerts
|

Household environmental safety and perceived stress among uninsured free clinic patients

Abstract: The purpose of this research project is to examine the association between household environmental safety and stress among uninsured primary care patients who live in poverty. Data were collected from patients of a free clinic using a self-administered survey in Fall 2019. A total of 559 patients participated in the survey. Higher levels of concern regarding environmental issues at home are associated with higher levels of perceived stress. The following demographic characteristics were associated with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Dissociation shields the individual from experiencing the full impact of trauma and keeps them away from the distress caused by the trauma. The findings are also in agreement with a literature studies that reported that dissociation is a product of a history of trauma and a coping strategy (Dinehart, Panahi, & Kamimura, 2021;Malmo & Laidlaw, 2010). In this case, the impact of trauma is less experienced with an increase in dissociation.…”
Section: Relationship Between the Impact Of The Memory Of Trauma And ...supporting
confidence: 92%
“…Dissociation shields the individual from experiencing the full impact of trauma and keeps them away from the distress caused by the trauma. The findings are also in agreement with a literature studies that reported that dissociation is a product of a history of trauma and a coping strategy (Dinehart, Panahi, & Kamimura, 2021;Malmo & Laidlaw, 2010). In this case, the impact of trauma is less experienced with an increase in dissociation.…”
Section: Relationship Between the Impact Of The Memory Of Trauma And ...supporting
confidence: 92%
“…Applications in distance education consist of synchronous, asynchronous, material sharing, e-learning, and blended learning, which take place in a wide variety of areas, such as through the use of online communication environments (such as Google Meet, Zoom, Microsoft Teams, etc.) or learning management systems [29,30]. Distance education is a learning-teaching platform supported by technology.…”
Section: Distance Educationmentioning
confidence: 99%